Performance of ultra-high-performance concrete incorporating municipal solid waste incineration fly ash. (December 2022) - Lv, Yajun; Yang, Longbin; Wang, Julian; Zhan, Baojian; Xi, Zhuangmin; Qin, Yiming; Liao, Dang
Abstract: The dioxin in waste fly ash is highly toxic, posing a difficult problem for its treatment. Improper treatment can lead to substantial potential safety hazards. In this research, a high-temperature treatment was applied to degrade the dioxin in waste fly ash which was reduced to 1/1209 of the untreated level. Then, based on an Andreasen and Andersen model, the waste fly ash was used to prepare ultra-high-performance concrete (UHPC). The effects of the municipal solid waste incineration (MSWI) fly ash treated with high temperatures on UHPC's fluidity, hydration process, mechanical properties, and microstructure and the binding capacity of heavy metal ions were investigated. The experimental results revealed that for volume replacement rates of cement ≤ 20%, the incorporation of high-temperature treated MSWI fly ash accelerated the UHPC hydration process, reduced the fluidity, and shortened the setting time. The 28-day compressive strength of UHPC was increased due to the inclusion of high-temperature treated MSWI fly ash but varied little with the increasing content of ash. The UHPC pores were generally harmless, below 20 nm, exhibiting obvious binding effects on heavy metal ions. The results suggest the potential of high-temperature treated MSWI fly ash as a substitute for cement during UHPC preparation.